High p16 Expression Is Associated with Malignancy and Shorter Disease-Free Survival Time in Solitary Fibrous Tumor/Hemangiopericytoma - Liang, Yuanxin; Heller, Robert S.; Wu, Julian K.; Heilman, Carl B.; Tischler, Arthur S.; Arkun, Knarik (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Solitary fibrous tumors (SFT) and hemangiopericytomas (HPC) are now classified along a single spectrum of fibroblastic mesenchymal tumors with NAB2–STAT6 fusion. This fusion acts as a driver mutation that constitutively activates EGR1, which is known to be involved in the p16 pathway. Overexpression of p16 is associated with malignancy and worse prognosis in multiple mesenchymal tumors. The authors sought to investigate p16 immunoexpression in association with malignancy and prognosis of SFT/HPC tumors.Design Twenty-three SFT/HPC tumors (central nervous system [CNS]: 12, non CNS: 11) diagnosed at our institution from 2002 to 2016 were assigned into 3 grades. Data from microarray immunohistochemistry for STAT6, synaptophysin, CD56, chromogranin, SST2A, EGR1, Ki67, and p16, grade and survival were analyzed.Results CNS SFT/HPCs tend to be malignant (grade 3; 67 vs. 18%, p = 0.036) and more likely to express synaptophysin (33 vs. 0%, p = 0.035) than non CNS tumors. Overexpression of p16 (immunopositivity ≥ 50% tumor cells) was associated with malignant (grade 3) tumors, and has a sensitivity of 70% (7/10), and a specificity of 77% (10/13), as a predictive marker for malignancy. SFT/HPC patients with low p16 expression demonstrated significantly longer disease-free survival time (median survival > 113 months) than those with high p16 expression (median survival = 30 months, p = 0.045).Conclusions SFT/HPCs in the CNS are more likely to be malignant than the tumors in other sites. High p16 expression is also associated with malignancy and shorter disease-free survival time in SFT/HPC tumors in our study cohort. Clinically, p16 overexpression can be used as predictive marker for malignancy and prognosis and a possible therapeutic target.
Keywords: solitary fibrous tumor; hemangiopericytoma; p16; malignancy; disease-free survival time